Application of Olive Oil Administration in Overcoming Skin Integrity Disorders in Mrs. V with CKD ON HD on the 6th Floor of the Darmawan Pavilion, RSPAD Gatot Soebroto - Syaefudin, Didin (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Chronic Kidney Failure is a decrease in kidney function on a small scale, chronic kidney failure can occur abnormalities where the decline in kidney function occurs progressively causing various complaints from mild to severe. The purpose of this case study describes the application of olive oil administration in overcoming skin integrity disorders in Mrs. V with CKD ON HD using the nursing process. Method This case study uses a descriptive method in the form of a single case study conducted on one patient with a diagnosis of CKD ON HD on the VI Floor of the Darmawan Pavilion, RSPAD Gatot Soebroto using data collection techniques, namely observation, interviews, and documentation studies. The results of the case study obtained after applying the action of administering olive oil to overcome skin integrity disorders to clients for 5x24 hours obtained the results of the evaluation of clinical signs of itching decreased, the scale of pruritus decreased, some dry skin decreased. The conclusion of this case study after conducting a case study, the results showed that the application of olive oil administration to CKD ON HD patients had an effect on overcoming skin integrity disorders in Mrs. V.